Enhancing Science Process Skills in Fifth-Grade Students at SD Negeri 5 Unggul Tapaktuan through Experimental Methods in Heat Transfer Material Application - Khairi, Miftahul (Lembaga KITA, 2023)
This study was prompted by the observed inadequacy in students' science process skills during learning activities, attributed to the utilization of inappropriate teaching methods that fail to offer a comprehensive understanding of the material. Consequently, these methods struggle to engage students' interest and curiosity effectively. The primary objective of this research is to assess the enhancement of students' science process skills through the implementation of the experimental method, focusing on the science subject of heat transfer material. Employing a true experimental research design with a posttest-only control group, the study unfolded during the second semester of the academic year 2022/2023, specifically from May 16 to 21. The participants comprised two classes: Class VB as the experimental group and Class VA as the control group. Data collection utilized an observation sheet for students. The analysis of data to evaluate science process skills employed the percentage formula. The findings revealed a substantial increase in science process skills, as evidenced by the experimental class's post-test scores rising from 54% to 98%. This indicates a noteworthy improvement of 44% attributable to the application of the experimental method in heat transfer material. In conclusion, the study affirms that employing experimental methods in heat transfer material significantly enhances students' science process skills, validating a substantial and statistically significant increase in their proficiency.